2017
DOI: 10.1016/j.bandl.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A common neural hub resolves syntactic and non-syntactic conflict through cooperation with task-specific networks

Abstract: Regions within the left inferior frontal gyrus (LIFG) have simultaneously been implicated in syntactic processing and cognitive control. Accounts attempting to unify LIFG’s function hypothesize that, during comprehension, cognitive control resolves conflict between incompatible representations of sentence meaning. Some studies demonstrate co-localized activity within LIFG for syntactic and non-syntactic conflict resolution, suggesting domain-generality, but others show non-overlapping activity, suggesting doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 114 publications
(210 reference statements)
4
51
0
Order By: Relevance
“…According to the Memory-Unification-Control (MUC) model (Hagoort, 2013(Hagoort, , 2016, a control mechanism in language processing is located in the left dorsolateral prefrontal cortex (DLPFC). The MUC model is supported by functional magnetic resonance imaging (fMRI) studies reporting activation of the left DLPFC during sentence comprehension (Cooke et al, 2006;Hashimoto & Sakai, 2002;Hsu, Jaeggi, & Novick, 2017;Makuuchi, Bahlmann, Anwander, & Friederici, 2009;Stephens, Silbert, & Hasson, 2010) and sentence production (Humphreys & Gennari, 2014). To examine the functional nature of the neural activation patterns more directly, transcranial direct current stimulation (tDCS) is used to directly influence the cortical areas during language processing (Joyal & Fecteau, 2016;Price, McAdams, Grossman, & * Address correspondence to Jana Klaus (j.klaus@donders.ru.nl).…”
mentioning
confidence: 98%
“…According to the Memory-Unification-Control (MUC) model (Hagoort, 2013(Hagoort, , 2016, a control mechanism in language processing is located in the left dorsolateral prefrontal cortex (DLPFC). The MUC model is supported by functional magnetic resonance imaging (fMRI) studies reporting activation of the left DLPFC during sentence comprehension (Cooke et al, 2006;Hashimoto & Sakai, 2002;Hsu, Jaeggi, & Novick, 2017;Makuuchi, Bahlmann, Anwander, & Friederici, 2009;Stephens, Silbert, & Hasson, 2010) and sentence production (Humphreys & Gennari, 2014). To examine the functional nature of the neural activation patterns more directly, transcranial direct current stimulation (tDCS) is used to directly influence the cortical areas during language processing (Joyal & Fecteau, 2016;Price, McAdams, Grossman, & * Address correspondence to Jana Klaus (j.klaus@donders.ru.nl).…”
mentioning
confidence: 98%
“…Broca's region has been traditionally associated with verb processing across tasks such as verb-specific morphological transformation (Sahin, Pinker, & Halgren, 2006;Shapiro et al, 2005Shapiro et al, , 2006, action processing (Caspers et al, 2010), lesion studies of action picture naming (Damasio & Tranel, 1993) and verb semantics (Kemmerer et al, 2012). Although Broca's area activations were specific to verbs in the present ALE analysis, it is important to point out that Broca's area is associated with numerous cognitive operations, including language selective and domain general operations, such as math, music, cognitive control and working memory (Fedorenko, Behr, & Kanwisher, 2011;Fedorenko, Duncan, & Kanwisher, 2012;Hsu, Jaeggi, & Novick, 2017). Given Broca's area's role in numerous neuroimaging studies of syntactic processing (see Friederici, 2011 for a review) and patients with syntactic deficits (Faroqi-Shah et al, 2014), it is likely that these two verb selective regions subserve different aspects of verb processing: BA21 for verb representations and BA44/45 for implementing a verb's syntactic constraints.…”
Section: Verbs and Nouns Have Unique Representationsmentioning
confidence: 62%
“…Given Broca's area's role in numerous neuroimaging studies of syntactic processing (see Friederici, 2011 for a review) and patients with syntactic deficits (Faroqi-Shah et al, 2014), it is likely that these two verb selective regions subserve different aspects of verb processing: BA21 for verb representations and BA44/45 for implementing a verb's syntactic constraints. Although Broca's area activations were specific to verbs in the present ALE analysis, it is important to point out that Broca's area is associated with numerous cognitive operations, including language selective and domain general operations, such as math, music, cognitive control and working memory (Fedorenko, Behr, & Kanwisher, 2011;Fedorenko, Duncan, & Kanwisher, 2012;Hsu, Jaeggi, & Novick, 2017). This cluster included parts of the insula (BA13), whose lateral aspect is interspersed between BA44 and BA45.…”
Section: Verbs and Nouns Have Unique Representationsmentioning
confidence: 64%
“…In addition, we focused on two cognitive domains which have shown to be particularly susceptible to the effects of N-back training; specifically, we included measures of inhibitory control, interference resolution (Soveri et al 2017; Novick et al 2014), and visuospatial reasoning (Au et al 2015; Jaeggi et al 2014). Previous work has demonstrated that those domains share common variance with the N-back task and that they rely on similar neural networks (Hsu et al 2017; Jaeggi et al 2010; Szmalec et al 2011). Furthermore, an exploratory portion of our study investigated the generalization potential of N-back training to more applied measures.…”
Section: Methodsmentioning
confidence: 99%
“…Given the shared variance of N-back and various measures of inhibitory control and interference resolution (Hsu et al 2017; Szmalec et al 2011), we included two measures to capture training-related improvements in those domains and any differential effects as a function of training type.…”
Section: Methodsmentioning
confidence: 99%